2011
DOI: 10.1073/pnas.1105892108
|View full text |Cite
|
Sign up to set email alerts
|

Lotus japonicus nodulation is photomorphogenetically controlled by sensing the red/far red (R/FR) ratio through jasmonic acid (JA) signaling

Abstract: Light is critical for supplying carbon to the energetically expensive, nitrogen-fixing symbiosis between legumes and rhizobia. Here, we show that phytochrome B (phyB) is part of the monitoring system to detect suboptimal light conditions, which normally suppress Lotus japonicus nodule development after Mesorhizobium loti inoculation. We found that the number of nodules produced by L. japonicus phyB mutants is significantly reduced compared with the number produced of WT Miyakojima MG20. To explore causes other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
91
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 107 publications
(98 citation statements)
references
References 40 publications
5
91
0
Order By: Relevance
“…By using grafted plants prepared from MG20 and phyB mutant plants, we also showed that shoot genotype controls root nodule formation. 9 Here we report additional data confirms that root nodulation is controlled by shoot genotype. The expression level of marker gene NIN, 10 which is required for infection thread formation and nodule primordium initiation, was analyzed in the root of grafted plants by using real time RT-PCR by the methods described in Tominaga et al 11 The roots and shoots of five-day-old MG20 and phyB mutant plants were grafted in various combinations, as described by Magori et al 12 After 7 d, the grafted plants were inoculated with M. loti, and expression was analyzed 7 d after inoculation.…”
Section: -8supporting
confidence: 70%
See 2 more Smart Citations
“…By using grafted plants prepared from MG20 and phyB mutant plants, we also showed that shoot genotype controls root nodule formation. 9 Here we report additional data confirms that root nodulation is controlled by shoot genotype. The expression level of marker gene NIN, 10 which is required for infection thread formation and nodule primordium initiation, was analyzed in the root of grafted plants by using real time RT-PCR by the methods described in Tominaga et al 11 The roots and shoots of five-day-old MG20 and phyB mutant plants were grafted in various combinations, as described by Magori et al 12 After 7 d, the grafted plants were inoculated with M. loti, and expression was analyzed 7 d after inoculation.…”
Section: -8supporting
confidence: 70%
“…9 In that paper, we concluded that the cause of reduced root nodule formation in low-R/FR-grown MG20 (wild-type) plants and white-light-grown phyB mutants is inhibition of JA-Ile (an active JA derivative) production in root. By using grafted plants prepared from MG20 and phyB mutant plants, we also showed that shoot genotype controls root nodule formation.…”
Section: -8mentioning
confidence: 99%
See 1 more Smart Citation
“…5). 49) It was further observed that the phyB mutant plants set the first flower at the 7th node on average, while wild-type plants did so at the 13th node on average. This event observed for phyB is a hallmark of the early flowering phenotype.…”
Section: Is the Red Light Photoreceptor Ljphyb Implicated In The Contmentioning
confidence: 96%
“…Recently, a stable phyB (the gene encoding one of the red light photoreceptors) mutant of L. japonicus was isolated and characterized in terms of a linkage between nodulation in roots and far-red response in shoots. 49) The phyB mutant allowed us to characterize the L. japonicus plant itself with special reference to the flowering time. It is well known of A. thaliana that the phyB photoreceptor regulates (or inhibits) flowering through AtFT in response to changes in light quality.…”
Section: Is the Red Light Photoreceptor Ljphyb Implicated In The Contmentioning
confidence: 99%